La lucidité, l'émotion. Entretien avec Nicole Brossard, poète et romancière - Brossard, Nicole; Saint-Martin, Lori (Nouvelles Questions Féministes, 2004)
Nicole Brossard compte parmi les créatrices féministes les plus importantes du Québec contemporain. Née en 1943, elle a publié une trentaine de recueils de poésie, neuf romans et des proses diverses. Elle a remporté les plus grands prix littéraires du Canada, dont le prix Athanase-David, le prix du Gouverneur général, le Grand Prix de Poésie du Festival international de Trois-Rivières et, en 2003, le prix W. O. Mitchell. Traduits en plusieurs langues, repris dans des anthologies et étudiés par les universitaires, ses textes ont inspiré de nombreuses femmes du Québec et d’ailleurs.
Keywords: amériques; approches et analyses; patriarcat; poésie; québec; ressource en ligne; roman; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*

L'hermaphrodite et la bisexualité à l'épreuve du droit dans l'antiquité - Cantarella, Eva (Diogène, 2004)
Traduit de l’italien.
Keywords: LGBTQIA2+; androgynie; antiquité; approches et analyses; bisexualité; cours; discipline; discours dominant; europe; grèce; grèce antique; his4860; homosexualité; identités LGBTQIA2+; intersexuation; inégalités; moeurs sexuelles; mythologie; patriarcat; premier cycle; périodes historiques; rapports sociaux; rome antique; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Patriarcat (Théorie du) - Delphy, Christine (Dictionnaire critique du féminisme, 2004)
Keywords: approches et analyses; cours; discipline; europe; fem1000; france; féminisme matérialiste; outils; ouvrages de références; patriarcat; premier cycle; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

Public/Privé - Lamoureux, Diane (Dictionnaire critique du féminisme, 2004)
Keywords: approches et analyses; cours; discours dominant; fem1000; histoire et politique; maternité; mouvements féministes; outils; ouvrages de références; patriarcat; premier cycle; systèmes d'oppressions; thématiques

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Rowman & Littlefield, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Section: x, 193 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

Le masculinisme de « La domination masculine » de Bourdieu - Thiers-Vidal, Léo (2004)
Keywords: antiféminisme; approches et analyses; cours; discipline; fem1000; masculinisme; patriarcat; premier cycle; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions